The Return Of Orality In Indonesian Literature In The Age Of Digital Literacy - Budiman, Manneke (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
This paper argues that contemporary Indonesian literature has been witnessing the return of some key elements of orality despite, or exactly because of, the advent of the digital era. Orality, which is supposed to have been fading out since the introduction of print literacy, seems to have been brought back to life as we enter the digital age rather than fade away further. This is visible particularly in the use of vernacular and conversational language in dialogues, heightened by the use of rural settings and unreliable narrators/characters. Such a renewed interest in orality among writers helps enrich the variety and heterogeneity of contemporary Indonesian literature in the last decade.